Implementasi media multisensorik berbasis view scan, auris, dan mechano receptor untuk meningkatkan fungsi kognitif siswa tunanetra di SLB Negeri Lamongan - Darmayanti, Novi; Irawan, Mohamad Rizal Nur; Haryono, Heny Ekawati; Anggraeni, Fitri Dwi; Fachruddin, Fanny Evanda (Penamas: Journal of Community Service, 2025)
This Community Service (PkM) activity was motivated by the limited availability of innovative learning media for visually impaired students, who generally rely only on audio or braille. The purpose of this program is to develop and implement multisensory learning media based on View Scan, Auris, and Mechano Receptor to enhance the cognitive functions of visually impaired students at SLB Negeri Lamongan. The novelty lies in integrating visual, auditory, and tactile technologies into a structured learning system, thereby improving accessibility and learning effectiveness. The method used was a quantitative, experimental design approach. The subjects were visually impaired students, with data collected through observation, pre- and post-cognitive tests, and documentation. Data analysis was carried out descriptively and inferentially. The results showed a positive response: View Scan supported object identification, Auris reinforced verbal comprehension, and the Mechano Receptor improved spatial perception. Students’ participation, concentration, and memory increased significantly, with an effectiveness rate of 81.01%. In conclusion, this PkM successfully enhanced the cognitive functions of visually impaired students.